2021
DOI: 10.3390/ani11020331
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stroking on Serotonin, Noradrenaline, and Cortisol Levels in the Blood of Right- and Left-Pawed Dogs

Abstract: It has been assumed that stroking relieves stress responses in dogs, and dogs with the activation of the left-brain hemisphere (right-pawed) may show better adaptation to stress conditions. The aim of the study was to determine whether the stroking stimulus induced changes in the level of selected neuroregulators in dogs’ blood and whether these changes depended on the sex and the predominance of the activity of one of the brain hemispheres. The study involved 40 dogs of various breeds and both sexes. The expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 70 publications
2
2
0
Order By: Relevance
“…Endocrine balance, reflected in the level of neurotransmitters, is the key factor necessary to ensure homeostasis (Karpiński et al, 2021). Differences were shown in the concentration of dopamine (DA) and dopaminergic receptors in dominant and subordinate hens (Cheng et al, 2002), which was confirmed by the present results.…”
Section: Discussionsupporting
confidence: 85%
“…Endocrine balance, reflected in the level of neurotransmitters, is the key factor necessary to ensure homeostasis (Karpiński et al, 2021). Differences were shown in the concentration of dopamine (DA) and dopaminergic receptors in dominant and subordinate hens (Cheng et al, 2002), which was confirmed by the present results.…”
Section: Discussionsupporting
confidence: 85%
“…Physical and/or psychological frustration can turn German Shepherds into introverted, exaggeratedly territorial, aggressive, or even compulsive animals. In the current study, three of 18 German Shepherd dogs showed aggressive behavior, and the same dogs also showed dopamine and serotonin values below the threshold and values related to stress (i.e., norepinephrine and beta-endorphins) above the threshold suggesting a relationship between the levels of neurotransmitters and the aggressive behavior as previously shown [14,[34][35][36].…”
Section: Discussionsupporting
confidence: 82%
“…In the research conducted by Karpiński, M. et al [ 39 ], it was found that the plasma noradrenaline, cortisol, and serotonin levels were lower in female dogs than in males. Additionally, the plasma noradrenaline and serotonin levels were higher in the right-pawed dogs than in the left-pawed dogs.…”
Section: Discussionmentioning
confidence: 99%